Perancangan Sistem Perpustakaan Digital Model Waterfall Pada Sekolah Menengah Kejuruan Negeri 2 Limboto - Farid F (Program Vokasi Universitas Negeri Gorontalo, 2026)
The existing system has not integrated interactive features such as rating and review mechanisms. Without these features, library managers have difficulty evaluating the quality or relevance of collections from a user perspective. The purpose of this research focuses on developing a digital library website that allows users to search for books, read digital content, and provide ratings and reviews. The system was developed using the Waterfall method and implemented with PHP and MySQL. The results of the study indicate that the system can improve the efficiency of book data management and facilitate user access to digital library services. [Reviewer13.1] Blackbox testing of the system was conducted to ensure that all modules run according to the requirements specifications. Based on testing of the main features (including search, upload, and rating), the application was found to be faster in data processing and error